2013
DOI: 10.1177/1535370213480740
|View full text |Cite
|
Sign up to set email alerts
|

Collagen hydrolysate inhibits zymosan-induced inflammation

Abstract: During the past years, evidence accumulated showing that glycine comprises anti-inflammatory activities. These effects occur, at least in part, via the activation of glycine-gated chloride channels (GlyR). Glycine is one of the major structural units of collagen, making up about 30% of the amino acids. This study aims to investigate the anti-inflammatory potential of collagen hydrolysate (CH) using the zymosan-induced ear-skin inflammation mouse model. After oral intake of 12.5, 25 or 50 mg CH the plasma level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…A direct antiinflammatory potential of collagen peptides is discussed that could also lead to decreased joint pain intensity. This hypothesis is supported by preclinical experiments, which have demonstrated that collagen peptide supplementation induces a glycine-mediated inhibition of cytokine release (Hartog et al 2013).…”
Section: Discussionsupporting
confidence: 65%
“…A direct antiinflammatory potential of collagen peptides is discussed that could also lead to decreased joint pain intensity. This hypothesis is supported by preclinical experiments, which have demonstrated that collagen peptide supplementation induces a glycine-mediated inhibition of cytokine release (Hartog et al 2013).…”
Section: Discussionsupporting
confidence: 65%
“…Hydrolysates of collagen and gelatin have also been reported to have potential anti‐inflammatory activity (Hartog, Cozijnsen, DE Vrij, & Garssen, ; Kouguchi et al, ; Ramadass et al, ; Sae‐leaw et al, ). Indeed, Sae‐leaw et al () reported that the Alcalase hydrolysis of seabass skin gelatin produced hydrolysates with anti‐inflammatory activity in RAW264.7 cells, decreasing levels of the pro‐inflammatory cytokines interleukin (IL)‐6 and IL‐1ÎČ.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Sae‐leaw et al () reported that the Alcalase hydrolysis of seabass skin gelatin produced hydrolysates with anti‐inflammatory activity in RAW264.7 cells, decreasing levels of the pro‐inflammatory cytokines interleukin (IL)‐6 and IL‐1ÎČ. A commercial collagen hydrolysate (Colnatur) has been reported to inhibit zymosan‐induced inflammation in mice and decreased the production of IL‐6 in whole blood cells (Hartog et al, ). Collagen, from chicken feet hydrolyzed using a fungal protease, produced peptides that inhibited tumor necrosis factor (TNF)‐α induced inflammation in human endothelial cells in culture (Kouguchi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of glycine in inhibiting proinflammatory cytokine expression have been studied in vitro and confirmed in different animal models, especially for beneficial effects in reducing pain in OA of the hip and knee. 38 Apart from glycine, there is a relation between the intake of collagen and hydroxyproline levels in human plasma. Hydroxyproline is an amino acid specifically present in collagen, and studies 39 have shown that its presence in the plasma inhibits mineralization chondrocytes and modulates the expression of the RUNX1 gene (runt-related transcription factor 1) and osteocalcin, stimulates the production of hyaluronic acid in the synovial cell cultures and increases the production of skin fibroblasts in rats.…”
mentioning
confidence: 99%
“…In order to evaluate the anti-inflammatory potential of glycine, Hartog et al 38 administered CH in different amounts, leading to ear inflammation in mice. CH was administered daily by oral gavage in the following amounts: control (0); 12.5, 25 and 50mg for three consecutive days, and inflammation was induced on the third day by the intra-dermal injection of zymosan.…”
mentioning
confidence: 99%